Impaired concentration of attention among to pupils of the second stage of primary school- (fourth and fifth years of primary stage) - Hadjdoudou , Meryem; Ismaili , Yamna (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
The current study aimed to know the level of attention deficit disorder among students of the second phase of the primary stage،in addition to detecting whether there are statistically significant differencesdue to the gender variable. theu were selected in a simple random way from Siddiq, Ghadban bin Soucha, Abdelhamid bin Badis،bin Makhfi Muhammad, Lamrad Khedi, Sassi Lakhdar).in addition to the use of descriptive approach as it is appropriate to the nature of this study،the attention concentration questionnaire was also applied to identify these students and measure the level of poor concentration of attention they have،as well as the nature of the differences between the gender (male-female) nweamness of concentration of attention among students of the second round of the primary stage is high, as well as the absence of statistically significant differences in the weakness of concentration of attention among students of the second stage of the primary stage due to the gender variable (male-female). based on that،the importance of addressing this phenomen in low academic achievement of students،especially in the primary stage،due to the imbalance in the function of attention and weakness of its focus clearly through the low school results and the complaints of parents about the level of concentration of the attention of their children without forgetting the teachers observation in the lessons as well as the continuous evaluations